A RIETE registry analysis of patients with upper extremity deep vein thrombosis and thoracic outlet syndrome. Issue 213 (May 2022) - Rosa, Vladimir; Chaar, Cassius Iyad Ochoa; Espitia, Olivier; Otalora, Sonia; López-Jiménez, Luciano; Ruiz-Sada, Pablo; Verhamme, Peter; Muñoz-Torrero, Juan Francisco Sánchez; Marchena, Pablo Javier; Monreal, Manuel; ,
Abstract: Background: Upper extremity deep vein thrombosis (UEDVT) related to thoracic outlet syndrome (TOS) is rare, and the literature is limited to institutional case series. Methods: We used data from the RIETE Registry to compare outcomes (recurrences, major bleeding and signs and symptoms of post-thrombotic [PTS] syndrome) in patients with UEDVT and TOS undergoing first rib resection vs. those not undergoing surgery. Results: From March 2001 to March 2021, there were 4214 patients with UEDVT, of whom 209 (4.96%) had TOS. Of these, 55 (26%) underwent first rib resection. Patients with TOS were younger and less likely to have comorbidities than those without TOS. There were no differences between patients with TOS undergoing surgery and those who did not. During anticoagulation, patients with TOS had a non-statistically significant lower rate of VTE recurrences than those without TOS (hazard ratio [HR]: 0.46; 95%CI: 0.14–1.12) and a lower bleeding rate (HR: 0.16; 95%CI: 0.01–0.83). No patient with TOS developed pulmonary embolism or died. Patients with TOS undergoing surgery had fewer PTS symptoms (odds ratio [OR]: 0.21; 95%CI: 0.06–0.68) or signs (OR: 0.11; 95%CI: 0.02–0.42) after one year than patients who did not have surgery. At two years, the differences in symptoms (OR: 0.25; 95%CI: 0.06–0.94) and signs (OR: 0.04; 95%CI: 0.002–0.33) persisted. Conclusions: Patients with UEDVT and TOS were younger and had less comorbidities than those without. Surgical resection of the first rib was associated with a lower proportion of patients developing PTS one and two years later. Highlights: The RIETE registry, 4.96% of patients with UEDVT had documented TOS. Patients with UEDVT and TOS are younger and have less comorbidities. First rib resection is associated with decreased PTS symptoms in patients with TOS.